2020
DOI: 10.1007/978-981-15-3750-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Reliable Machine Learning-Based Global Misbehavior Detection in C–ITS: Model Evaluation Approach

Abstract: Global misbehavior detection in Cooperative Intelligent Transport Systems (C-ITS) is carried out by a central entity named Misbehavior Authority (MA). The detection is based on local misbehavior detection information sent by Vehicle's On-Board Units (OBUs) and by RoadSide Units (RSUs) called Misbehavior Reports (MBRs) to the MA. By analyzing these Misbehavior Reports (MBRs), the MA is able to compute various misbehavior detection information. In this work, we propose and evaluate different Machine Learning (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It should be noted that the primary objectives of the proposed system are to process video footage for recognizing risks with the predicted road-user trajectories in real time and to alleviate the data flow issues in conventional systems that handle road-related risks and phenomena [30,31]. However, when dealing with video data, characterized by its substantial file sizes and resource-intensive processing demands, transmitting data and retrieving information can be time-consuming.…”
Section: Results Of the Time Effectiveness Of The Proposed System And...mentioning
confidence: 99%
“…It should be noted that the primary objectives of the proposed system are to process video footage for recognizing risks with the predicted road-user trajectories in real time and to alleviate the data flow issues in conventional systems that handle road-related risks and phenomena [30,31]. However, when dealing with video data, characterized by its substantial file sizes and resource-intensive processing demands, transmitting data and retrieving information can be time-consuming.…”
Section: Results Of the Time Effectiveness Of The Proposed System And...mentioning
confidence: 99%
“…Their proposal on vehicle trust model requires a central Trust Authority (TA) as well as a local vehicle trust module to combine different assessments. Some other studies were inspired by the public dataset VeReMi and simulated their own scenarios to create new attack types for their approaches [28]- [30]. They also generated several other features (e.g.…”
Section: B Ml-based Detection Mechanisms In Vanetsmentioning
confidence: 99%
“…Four features were considered to detect the attack geographical position validation: acceptance field verification, speed variation verification, and received signal strength. Issam Mahmoudi et al [6] proposed a ML-based global misbehavior detection system to analyze the reported misbehavior sent by vehicles and Roadside Units (RSU). A set of algorithms was trained to assess the detection based on a few selected features: (i) plausibility and consistency check features, (ii) communication kinematic data features, and (iii) generic features.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, vehicular networks have benefited from the advances in machine learning in the areas of network security. Indeed, several ML-based Misbehavior Detection Systems (ML-based MDSs) have been proposed for the efficient detection of false position attacks [5][6][7][8][9][10]. However, existing solutions leverage numerous features which increase the computational complexity and overhead.…”
Section: Introductionmentioning
confidence: 99%